196k views
0 votes
If f(x) = 5x – 3 and g(x) = 3x – 3, find f(x) – g(x). Please include full explanation

2 Answers

7 votes

Answer:

f(x) - g(x) = 2x

Explanation:

We have given two functions.

f(x) = 5x-3 and g(x) = 3x-3

We have to find their difference.

f(x)-g(x) = ?

Putting given values, we have

f(x) - g(x) =( 5x-3) - (3x-3)

Distribute negative sign over second parentheses,

f(x) - g(x) = 5x-3 -(3x)-(-3)

f(x) - g(x) = 5x-3-3x+3

f(x) - g(x) = 5x-3x-3+3

Adding like terms, we have

f(x) - g(x) = 2x+0

f(x) - g(x) = 2x which is the answer.

User Nxn
by
4.8k points
3 votes

Answer:

2x

Explanation:

f(x) – g(x)

f(x) = 5x – 3 and g(x) = 3x – 3

f(x)- g(x) = 5x – 3 -( 3x – 3)

Distribute the minus sign

5x -3 -3x+3

Combine like terms

5x-3x-3+3

2x

User Tony McCreath
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.